Scientific publication must be part of the undergraduated research planning - Isabel CF da Cruz (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
Online Brazilian Journal of Nursing, as an authoritative resource in the communication of scientific information, points out the purpose to promote the scientific publishing of the undegraduate students by fostering education and exchange.